DEVELOPMENT OF UKRAINIAN TERRITORIES WITHIN THE FRAMEWORK OF PARTNERSHIP WITH THE EUROPEAN UNION - Shebanin , V.S.; Kormyshkina , I.V. (The actual problems of regional economy development, 2025)
The article focuses on the prospects for the development of Ukraine's territories within the framework of partnership with the European Union (EU). The relevance of the research is determined by current challenges such as full-scale war, economic crises, and social instability, which necessitate a new approach to regional governance. The aim of the article is to analyze the interaction between Ukraine and the EU in the context of regional development and assess the impact of European integration processes on the socio-economic state of Ukrainian territories. The study employs the following methods: system analysis to evaluate international cooperation, a comparative approach to study the EU's experience in regional development, and a case-study method to analyze specific examples of collaboration between Ukrainian cities and regions and European partners. The results of the article show that the main areas of cooperation between Ukraine and the EU include the implementation of cross-border cooperation programs, integration into macro-regional strategies, and participation in international initiatives such as the European Alliance of Cities and Regions for the Reconstruction of Ukraine. In particular, the effectiveness of implementing programs like "Interreg Europe" and the importance of horizontal ties between municipalities for experience exchange and innovation introduction are highlighted. The scientific novelty of the study lies in a comprehensive analysis of current challenges and opportunities for Ukraine's integration into European structures through regional development. For the first time, the article systematizes key areas of international cooperation, emphasizing the role of reconstruction initiatives under wartime conditions. The practical significance of the study lies in the possibility of using the obtained results to develop regional development strategies, particularly in the context of attracting international aid and adapting European governance standards to Ukrainian realities. The research concludes that effective partnership with the EU facilitates infrastructure modernization, enhances regional competitiveness, and ensures sustainable economic growth. However, realizing these prospects requires further improvement of policies and integration processes at the regional level.